Real-World Evidence to Reinforce Clinical Trial Evidence in Health Technology Assessment: A Critical Review of Real-World Evidence Requirements from Seven Countries and Recommendations to Improve Acceptance - Katia Thokagevistk; Céline Coppo; Laetitia Rey; Amanda Carelli; Veronica Díez; Sarah Vaselenak; Liana Oliveira; Ajay Patel; Emilia Sicari; Teresa Ramos; Susanne Schach; Erika Schirghuber; et al. (Journal of Market Access & Health Policy)
Background: Real-world evidence (RWE) can reinforce clinical trial evidence in health technology assessment (HTA). Objectives: Review HTA bodies’ (HTAbs) requirements for RWE, real uses, and acceptance across seven countries (Brazil, Canada, France, Germany, Italy, Spain, and the United Kingdom) and outline recommendations that may improve acceptance of RWE in efficacy/effectiveness assessments and appraisals processes. Methods: RWE requirements were summarized based on HTAbs’ guidelines. Acceptance by HTAbs was evaluated based on industry experience and case studies. Results: As of June 2022, RWE methodological guidelines were in place in three of the seven countries. HTAbs typically requested analyses based on local data sources, but the preferred study design and data sources differed. HTAbs had individual submission, assessment, and appraisal processes; some allowed early meetings for the protocol and/or results validation, though few involved external experts or medical societies to provide input to assessment and appraisal. The extent of submission, assessment, and appraisal requirements did not necessarily reflect the degree of acceptance. Conclusion: All the countries reviewed face common challenges regarding the use of RWE. Our proposals address the need to facilitate collaboration and communication with industry and regulatory agencies and the need for specific guidelines describing RWE design and criteria of acceptance throughout the assessment and appraisal processes.